Camera traps and activity signs to estimate wild boar density and derive abundance indices. Issue 4 (12th December 2017) - Massei, Giovanna; Coats, Julia; Lambert, Mark Simon; Pietravalle, Stephane; Gill, Robin; Cowan, Dave
Abstract: BACKGROUND: Populations of wild boar and feral pigs are increasing worldwide, in parallel with their significant environmental and economic impact. Reliable methods of monitoring trends and estimating abundance are needed to measure the effects of interventions on population size. The main aims of this study, carried out in five English woodlands were: (i) to compare wild boar abundance indices obtained from camera trap surveys and from activity signs; and (ii) to assess the precision of density estimates in relation to different densities of camera traps. For each woodland, we calculated a passive activity index (PAI) based on camera trap surveys, rooting activity and wild boar trails on transects, and estimated absolute densities based on camera trap surveys. RESULTS: PAIs obtained using different methods showed similar patterns. We found significant between‐year differences in abundance of wild boar using PAIs based on camera trap surveys and on trails on transects, but not on signs of rooting on transects. The density of wild boar from camera trap surveys varied between 0.7 and 7 animals/km 2 . Increasing the density of camera traps above nine per km 2 did not increase the precision of the estimate of wild boar density. CONCLUSION: PAIs based on number of wild boar trails and on camera trap data appear to be more sensitive to changes in population size than PAIs based on signs of rooting. For wild boar densities similar to those recorded in this study, nine camera traps per km 2 are sufficient to estimate the mean density of wild boar. © 2017 Crown copyright. Pest Management Science © 2017 Society of Chemical Industry Abstract : As wild boar impact increases worldwide, reliable methods are needed to assess local densities and population trends. This study presents methods to estimate wild boar density and abundance indexes.